Use of an Endobronchial Blocker and Selective Lung Ventilation to Aid Surgical Removal of a Lung Lobe Abscess in a Dog - Carl Bradbrook; Louise Clark; Martina Mosing (Case Reports in Veterinary Medicine)
This paper documents use of an endobronchial blocker (EBB) to achieve selective lung ventilation (SLV) for the purpose of lung lobectomy with thoracoscopy. A 3-year-old female neutered Labrador Retriever, body mass of 18.5 kg, was presented for exploratory thoracoscopy. Acepromazine and methadone were administered as premedication, and anaesthesia was induced with propofol and maintained with isoflurane in 100% oxygen and continuous infusions of fentanyl and lidocaine. Mechanical ventilation of the dog’s lungs was performed prior to placement of an Arndt EBB caudal to the right cranial bronchus to allow SLV. Successful SLV was achieved with this technique, allowing continued inflation of the right cranial lobe. A reduction in the arterial partial pressure of oxygen to fractional inspired oxygen ratio (PaO2 : FiO2) of 444 to 306 occurred after placement of the EBB, with no change in monitored cardiopulmonary variables. F-shunt increased from 17.4% to 23.7% with a reduction in oxygen content (CaO2) of 20.0 to 18.7 mg dL-1, remaining within the physiologic range. Due to lung adhesions to the diaphragm, conversion to thoracotomy was required for completion of the procedure. This technique is challenging to perform in the dog. Arterial blood gas analysis should be performed to allow adequate monitoring of ventilation.